Investigation of the nitrate loading characteristics of an agricultural watershed using a distributed eco-hydrogeological model - Sytharith Pen; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Nitrate is one of the most widespread contaminant in agriculture watershed. Nitrate could cause detrimental effect on human health and eutrophication of the water body. Siniloan watershed is a contributor to Laguna Lake, the largest lake in the Philippines. The excessive amount of nutrient to Laguna Lake will deterioratewater quality of the lake. The study of nitrate loading in this watershed is significant since there is urban area at the lower downstream of the watershed while there is active farming practices and agricultural areas on the upstream. Watershed models have become a main tool in addressing a wide spectrum of environment and water resources planning, development, operation, and management. Soil and Water Assessment Tool was employed to model the stream flow and nitrate loading from this watershed. The model was calibrated with uncertainty analysis using SUFL-2 based on model flow and monthly observed nitrate concentration at the outlet of the watershed. The results of daily stream flow calibration (RSR=0.44, NSE=0.78, Pbias=11.79) and validation (RSR=0.66, NSE-0.55, Pbias- 21.37) were quite satisfactory for the outlet of watershed. Nitrate leaching results in calibration (RSR=0.62, NSE=0.62, Pbias=21.15) and validation (RSR=0.67, NSE=0.54, Pbias=47.73) were also acceptable. The calibrated model was run under anthropogenic and climate variability. The model proves that farming operation such as reduction in fertilizer and grazing operation do not alter much stream flow but has effect on nitrate total yield. Crop rotation of rice and corn decreases nitrate yield by 4.56%. Deforestation increases both stream flow and nitrate transport. The decrease in rainfall by 20% and rising temperature (2.8°C, 4°C, and 1.8°C) reduce the stream flow in the range of 30% to 40% and elevate nitrate yield by about 30% in river. Nitrate leaching varies seasonally and spatially. Nitrate is washed off dramatically in wet season in agricultural area and most significant in dry season from urban area.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Soils -- Nitrate content